Do photos of police-civilian interactions influence public opinion about the police? A multimethod test of media effects - Wozniak, Kevin H. (Journal of experimental criminology, 2021)
Purpose To test whether exposure to news images depicting law enforcement affects public attitudes toward the police. Method Participants drawn from a national online panel were randomly assigned to view one of three pictures that depicted a range of hostile to friendly police-civilian interactions (compared to a control group who saw no pictures). Dependent variables were perceptions of police officers’ effectiveness, misconduct, and bias. Moderating variables were respondents’ experiential, ideological, or demographic characteristics. As a follow-up to the results of the experiment, regression analyses were employed to explore other factors that may influence perceptions of police or interact with the media effects. Results Image exposure did not directly affect any dimension of attitudes toward the police, but there was one significant moderation effect. Respondents who had been recently stopped by an officer and saw a picture of a friendly interaction between officers and a civilian perceived more frequent police misconduct than respondents in the same experimental condition who were not recently stopped. Routine media consumption was significantly related to perceptions of police in the non-experimental analysis. Conclusions Findings indicate that brief exposure to static images of law enforcement disseminated by the media does not independently affect people’s opinions about the performance of police in society. Rather, people’s global opinions about the police are shaped by their own beliefs, prior experiences with officers, and cumulative, self-selected media consumption.